2018
DOI: 10.1021/acs.langmuir.8b00905
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Porphine Supermolecules and Two-Dimensional Nanoaggregates Formed Using the Langmuir–Schaefer Technique

Abstract: Porphyrins are functional elements of important biomolecules, whose assemblies play a central role in fundamental processes such as electron transfer, oxygen transport, enzymatic catalysis, and light harvesting. Here we report an approach to formation of porphyrin supermolecules, a particular type of nanoparticles with unusually strong noncovalent intermolecular interactions. Key differences between the supermolecules and noncovalent nanostructures described earlier are as follows. (1) Supermolecules consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…It is shown that nanoaggregates of the complex more dense than nanoaggregates of the ligand (Figure 5a). The number of molecules in Cu[(ms-Ph) 3 Cor] aggregates more than the number of molecules in H 3 [(ms-Ph) 3 Cor] aggregates (by 2-3 times, Figure 5b). The rate of change the number of molecules in face-on and edge-on nanoaggregates with increasing of the initial surface coverage degree is 2-3 times greater for the complex than for the ligand (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is shown that nanoaggregates of the complex more dense than nanoaggregates of the ligand (Figure 5a). The number of molecules in Cu[(ms-Ph) 3 Cor] aggregates more than the number of molecules in H 3 [(ms-Ph) 3 Cor] aggregates (by 2-3 times, Figure 5b). The rate of change the number of molecules in face-on and edge-on nanoaggregates with increasing of the initial surface coverage degree is 2-3 times greater for the complex than for the ligand (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…The state of the Cu[(ms-Ph) 3 Cor] layer at the point A corresponds to «edge-on bilayer -tetralayer» (samples I and II, Figure 7). The state of the H 3 [(ms-Ph) 3 Cor] layer at the point B corresponds to «edge-on tetralayer» (sample III, Figure 7). (sh sol) = 1.9.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations